Importancia de la fertilización foliar con zinc y boro para mejorar la producción del cultivo de arroz (Oryza sativa L.) en la zona de Ventanas, Los Ríos - Zambrano Ganchozo, Jarelly Tais (2025)
Rice, is one of the most important crops worldwide. The main objective is to describe the importance of foliar fertilization with zinc and boron to improve the production of rice (Oryza sativa L.) in the Ventanas area, Los Ríos. The document compiled updated information from scientific articles and virtual libraries, through a non-experimental bibliographical research. The conclusions determined that there is no research related to foliar fertilization with zinc and boron in rice cultivation in the Ventanas area, Los Ríos province. The first symptoms of Zn deficiency in rice are the presence of small plants resulting from a shortage of growth regulators. When the deficiency begins, reddish spots are seen on the leaves, later larger spots of this color are seen, so it is necessary to apply zinc by foliar spraying; B deficiency causes a decrease in the plasticity of cell walls, preventing the division and elongation of cells in the meristematic tissues of the roots. The most characteristic symptoms are sterile spikes, hollow stems, poor grain development, leaves with elongated, watery or transparent stripes that later turn white and new, dead growth points. Its application stimulates plant growth, intervening in the flowering process and in the formation of the plant's root system, regulating its water content.